Karakteristik dimensi utama kapal pukat cincin di Pelabuhan Perikanan Pantai Tumumpa: Main dimension of purse-seiner at Tumumpa Coastal Fishing Port - Lembo, Liliyana; Pamikiran, Revols Dolfi Christian; Pangalila, Fransisco P. T.; Modaso, Vivanda O. J.; Dien, Heffry V.; Kalangi, Patrice N. I.; Silooy, Fanny; Budiman, Johnny (JURNAL ILMU DAN TEKNOLOGI PERIKANAN TANGKAP, 2024)
ABSTRACT The focus of this research is the Main Dimension Characteristics of Purse Seine Vessels based at the Tumumpa Coastal Fishing Port in Manado City, which includes the ratios or comparisons of the vessel's main sizes (LOA/BOA, LOA/D, and BOA/D), the relationships between the main sizes of the vessel (LOA vs BOA, LOA vs D, and BOA vs D), and the relationship of the main size of the vessel (LOA) with the carrying capacity (GT) and engine power (HP).The data analysis method was carried out using descriptive analysis through cross-tabulation and data presentation in the form of a curve of the relationship between the main ship sizes, the relationship between the main ship sizes, and the relationship between the main size of the ship's length (LOA) with load capacity (GT) and propulsion engine power (HP). Data analysis used the 'Curve Expert' application with a mathematical model: (1) the relationship between the main ship sizes using linear regression analysis Y=a+bx, and (2) the relationship between LOA with load capacity (GT) and propulsion engine power using non-linear regression analysis. The results of this study indicate that the comparison of the main dimensions of purse seine vessels in PPP Belang still has vessels that do not comply with the standard values proposed by Fyson (1985). There is a positive relationship between the main dimensions of the vessel (LOA/BOA, LOA/D, BOA/D) and between the main dimensions of the vessel (LOA) with load capacity (GT) and engine power (HP).